An approach to Euler-Mascheroni constant by Bernoulli numbers - Aygunes, Aykut Ahmet (AIP conference proceedings, 2020)
In this paper, we give two different versions of the Euler-Maclaurin summation formula. By using these formulae, we obtain special series including the Bernoulli numbers and Riemann zeta function. Consequently, we show that this series is calculated by Euler-Mascheroni constant. 2010 Mathematics Subject Classification. Primary 11B68; Secondary 65B15.